(untitled) (MIST International Journal of Science and Technology, 2025)
Managing land records is a fundamental duty of a government, ensuring the accuracy, consistency, integrity of ownership, and reliable transaction of data. Conventional paper-based or centralized digital technology-based land record systems are unable to hold the system trust, efficiency, and consistency, thus mostly demonstrate errors, fraud, and corruptions. On the other hand, blockchain technology presents a transformative solution. It offers transparent, tamper-proof, secure, and reliable approach for Land Record Management (LRM) system. In this study a blockchaindriven LRM system architecture with distributed ledger technology is presented. The proposed strategy enhances security and trust by ensuring transparency, acceptance, and accountability. The study also designs the smart-contracts algorithm in detail that facilitates land registration, ownership transfers, verification, and streamlining processes. The proposed architecture ensures automated functionalities with little human intervention, uplifting the system security. Moreover, the proposed blockchain architecture integrates finger-print biometric authentication that boosts the system strength in terms of security through identity verification. This mitigates the risks of errors, fraud, illegal modification, and unauthorized access. This article outlines a blockchain-based LRM framework and verified through implementation and testing, reflecting the potentiality of viable adoption of this advanced technology. MIJST, V. 13, December 2025: 47-63 https://doi.org/10.47981/j.mijst.13(02)2025.528(47-63)